PENGEMBANGAN PERANGKAT PEMBELAJARAN MEMPERBAIKI UNIT KOPLING DAN KOMPONEN-KOMPONEN SISTEM PENGOPERASIANNYA DENGAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI OTOMOTIF SMK NEGERI 2 TARAKAN - Mustaming, Akhmad; Cholik, Mochamad; Nurlaela, Luthfiyah (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT The background of this research is the lack of students' ability in acquiring the learning process at shool because do not have the feasible and effective learning set. One of the ways to help the students' understand the learning material of repairing clutch unit and its operation system component is by using the learning set which meets the curriculum 2013 and is based on the discovery learning model. This research aims to get the feasible and qualified learning set to be used, get the realibility in the learning process get the good realibility of the students, good students response for the materials of repairing clutch unit and its operations system component, and good students' study result. This research is conducted by using developmental design by using 4D model. They are define, design, develop, and dessiminate. It has two levels. The first step is developing the learning set by using discovery learning model. The secong step is try the learning set out fer the 25 automotive students at SMK Negeri 2 Tarakan. The result of this research shows that the developed learning set can be described as follows: (1) the learning set which is developed in the from of syllabus, lesson plan students' worksheet, scoring sheet, and the media is in the category of valid. The average score is 4.4, (2) the implementation of the learning set is in the good category. It is in a good category because is reliability score in the first try out is 0.92 and it becomes 0.95 in the second try out, (3) students' activities in the learning process is in the category of active. Its reliability score in the first try out is 0.94 and it becomes 0.95 in the second try out, (4) students' response is very positive. It score is 89.7% in the first try out and it becomes 89.7% in the second try out , (5) the classical accomplishment is achieved, either individually or classically. In general, it can be concluded that the earning set by using discovery learning which has been developed is feasible to be used and is effective to pass the students' study result. Keywords : Developing Discovery Learning Model based Learning Set, Curriculum 2013